Penerapan Sanksi Pidana Terhadap Pencemaran Lingkungan Yang Disebabkan Oleh Sampah di Kelurahan Lipat Kain Kecamatan Kampar Kiri Berdasarkan Undang-Undang Nomor 18 Tahun 2008 Tentang Pengelolaan Sampah - ', Surianti; ', Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Environmental pollution caused by waste can be allegedly violating Chapter XV article 39concerning criminal provisions in the Basic Law on Waste Management. However, the reality of pollution towaste in the Folding Kain village continues to occur and is getting worse. Enforcement of environmentalcriminal law does not go as it should, this is what proves that law enforcement that should provide adeterrent effect and prevent the occurrence of repetition of criminal acts or similar crimes has not runoptimally. The purpose of this thesis research is; First, to determine the application of criminal sanctionsagainst environmental pollution caused by garbage in the village of Lipat kain Kampar Kiri District,Second, to find out the obstacles and efforts faced in addressing environmental pollution caused by garbagein the District of Lipatkain Kampar Kiri District. From the results of the study there are two main problemsthat can be concluded. First, the application of criminal sanctions against environmental pollution causedby garbage in the Folding Kain Village in Kampar Kiri District is not running properly.Environmental pollution caused by garbage is regulated in Law Number 18 of 2008 concerningWaste Management, namely in CHAPTER XV article 39, but the application of sanctions carried out by theEnvironmental Service is still in the form of reprimand and garbage collection, sanctions imposed are not inaccordance with the Law or Applicable regulation. Secondly, the obstacles experienced by theEnvironmental Service in addressing environmental pollution caused by waste are in the form of lack ofawareness and knowledge of the residents of Lipat Kain Village on the law and the importance of theenvironment, the law enforcement factors, lack of personal and professionalism of law enforcement, lack offacilities and infrastructure adequate. And as for the efforts made by the Environmental Service inaddressing environmental pollution caused by waste, in the form of coordinating with the Kampar DistrictResort police, conducting socialization or counseling with the community, establishing good relations withthe community, installing banners or appointing, providing the necessary facilities in the case of wastemanagement such as garbage trucks, landfills, and personnel. Researcher's suggestion, First, it is suggestedto law enforcement officers to be able to apply the existing rules and the sanctions given are expected tohave a deterrent effect on the perpetrators of environmental pollution caused by garbage in order to createa clean and healthy environment. Secondly, it is expected that the Environment Service can implementmaximum prevention programs against environmental pollution, and work according to their respectiveprofessionalism.